Effect of date of seedling transplanting and fertility levels on potato (Solanum tuberosum) grown through true potato seed under north-east hill conditions - KAMLA SlNGH (Indian Journal of Agronomy, 2001)
A field experiment was conducted during the summer season of 1992 and 1993 at Shillong to find out optimum time of true potato seed (TPS) seedling transplanting and its fertilzier requirements. Seedling survival of potato (Solanum tuberosum L.) was higher (90%) in April transplanting. Significant higher tuberlet production was obtained with 15 April transplanted seedlings than delayed transplanting. Every in- crease in fertility level significantly increased the tuberlet production. Linear response to fertility levels was observed on all the dates of seedling transplanting. The highest (274.4 qlha) tuberlet production was obtained when seedling was transplanted on 15 April and supplemented with 160, 160 and 60 kglha of N, P,O, and K20 respectively. This treatment gave tuberlet production in ratio of 21 : 66 : 13 of large (> 80 g), medium (20-80 g) and small (< 20 g) respectively. The lowest (131.3 q/ha) tuberlet production was recorded when seedling was transplanted on 15 May and fertilized @ 80 kg N, 80 kg P20, and 60 kg K,O/ha. Size of tuberlet production was recorded in ratio of 9 : 71 : 20 with this treatment. More than 80% tuberlets were of marketable size (z 20 g) in all the treatments.